Pengembangan Fasiltas Dan Sumber Daya Masjid Untuk Mendukung Kegiatan Keagamaan Dimasjid Al-Anshr Desa Padang Ulak Tanjung - Juan, Rivhan; Sari, Mustika; Hazani, Meisi Putri; Anugrah, Fajar Hersan; Dian, Aulia; Hafis, Abdul; Cahyati, Syndi; Puspita, Dhita Ameli; Inayah, Sheren; Pracella, Aisha Yolanda (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Both the center of worship and the media for the development of the community as a whole. To support religious activities in Padang Ulak Tanjung village, the facilities of the Al-Anshr mosque are discussed in this paper. This study uses a qualitative descriptive approach through documentation, field notes, and interviews. The Al-Anshr Mosque in Padang Ulak Tanjung village is the place of research. The results of the study indicate that Al-Nashr in Padang Ulak Tanjung village is a mosque that has the ability to revive the spirit of the movement to support religious activities in the fields of religious spirituality, economy, education, social community, and the development of arts and culture. Community empowerment activities based on the mosque in Al-Anshr, Padang Ulak Tanjung village were successful thanks to adequate facilities and resources, as indicated by the ideal organizational structure of the mosque's board of directors, and the ability of the preachers to communicate well.